COVID-19 and (hydroxy)chloroquine: a dispute over scientific truth during Bolsonaro’s weekly Facebook live streams - Monari, Ana Carolina [UNESP]; Santos, Allan; Sacramento, Igor (Sissa Medialab Srl, 2020)
As successive studies have shown that chloroquine and hydroxychloroquine are ineffective in treating COVID-19, this article investigates how the Brazilian president, Jair Bolsonaro, disputes the truth around science to convince the population that these drugs can save lives, preserve jobs and restore economic growth. Using Charaudeau’s theory [2007; 2010] as a methodological framework, as well as understanding that right-wing populism has embodied post-truth communication as a distinctive feature of contemporary politics, we observed Bolsonaro’s weekly Facebook live streams — known as ‘lives’ — for 14 weeks, identifying them as a communicative device that offers Bolsonaro the material conditions to interact directly with his public. Finally, we structured our analysis according to the three most common themes — questioning delays due to an insistence on scientific methodology, overvaluation of personal experiences and emphasis on individuals’ freedom of choice — to observe the emotional images and discursive scenarios the Brazilian president stages to produce the intended pathemic effects of his discourse: hope and urgency; trust and distrust; freedom and polarization.
Keywords: Health communication; Science and media; Science communication in the developing world